PENGEMBANGAN EKONOMI LOKAL BERBASIS DIGITAL UNTUK MEWUJUDKAN TUJUAN PEMBANGUNAN BERKELANJUTAN DI CIREBON - Edy Setyawan; Hamzah Fansuri (LPPM Institut Pendidikan Nusantara Global, 2025)
Kalitengah Village, located in Tengah Tani District, Cirebon, holds an important yet underrecognized role in the history of Cirebon batik, with many renowned batik brands originating from this village. Despite having 119 batik SMEs, only 50 remain active today. To revive its legacy, the village government has initiated digital marketing-based training programs for batik entrepreneurs. Kalitengah is rich in batik heritage, notably the iconic Paksinagaliman motif, a symbol of multiethnic harmony: Paksi (Arab), Naga (Chinese), and Liman (Indian). This cultural blend adds uniqueness and high value to Kalitengah’s batik. The community service program employs a Community-Based Research approach, engaging locals throughout the process, focusing on technical training, continuous mentoring, and strengthening digital marketing. The aim is to improve the welfare of local batik artisans and entrepreneurs by transforming traditional mindsets into modern digital strategies. Skills taught include (a) using social media for brand awareness, (b) optimizing websites with SEO, (c) leveraging marketplaces for sales, (d) applying competitive pricing strategies, and (e) implementing influencer marketing. Several brands such as Batik Aqila, Batik Ajeng, and Batik Wike have begun adopting these digital strategies. Through this program, Kalitengah is expected to reclaim its place as a widely recognized center of Cirebon batik, empowered by innovation and digital strength.